A prognostic scoring system using inflammatory response biomarkers in oral cavity squamous cell carcinoma patients who underwent surgery-based treatment. (3rd April 2018) - Park, Young Min; Oh, Kyung Ho; Cho, Jae-Gu; Baek, Seung-Kuk; Kwon, Soon-Young; Jung, Kwang-Yoon; Woo, Jeong-Soo
Abstract: Background: The aim of this study was to evaluate the effectiveness of a scoring system based on the lymphocyte-to-monocyte ratio, neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio for predicting disease-specific survival of oral cancer patients treated by surgery. Methods: From January 2007 to December 2016, we retrospectively analyzed data from 69 oral cancer patients who received surgery. Results: Lymphocyte-to-monocyte ratio was significantly associated with T classification, N classification, and pathologic stage. Neutrophil-to-lymphocyte ratio was significantly associated with T classification and pathologic stage. Platelet-to-lymphocyte ratio was significantly associated with N classification and pathologic stage. In multivariate analysis, only a higher score on this scoring system was significantly associated with poorer disease-specific survival. Conclusions: We found that the prognostic score system based on these three values was significantly associated with disease-specific survival of oral cancer patients who received surgery, indicating that the prognostic scoring system was effective in indirectly predicting systemic inflammatory response.